Applications of Artificial Intelligence Techniques in Engineering SIGMA 2018, Volume 2 - Malik, Hasmat; Srivastava, Smriti; Sood, Yog Raj.; Ahmad, Aamir; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
The book is a collection of high-quality, peer-reviewed innovative research papers from the International Conference on Signals, Machines and Automation (SIGMA 2018) held at Netaji Subhas Institute of Technology (NSIT), Delhi, India. The conference offered researchers from academic and industry the opportunity to present their original work and exchange ideas, information, techniques and applications in the field of computational intelligence, artificial intelligence and machine intelligence. The book is divided into two volumes discussing a wide variety of industrial, engineering and scientific applications of the emerging techniques.
Chapter 1: A New Approach for Power Loss Minimization in Radial Distribution Networks -- Chapter 2: Security Constrained Unit Commitment for Joint Energy and Reserve Market based on MIP Method -- Chapter 3: In-depth analysis of Charge leakage through vegetation in transmission and distribution lines -- Chapter 4: Comparative Study of Different Neural Networks for One Year Ahead Load Forecasting -- Chapter 5: Reliability of PMU using Fuzzy - Markov Dynamic Method -- Chapter 6: A Hybrid Intelligent Model for Power Quality Disturbance Classification -- Chapter 7: DSTATCOM with T-connected Transformer for improving power Quality -- Chapter 8: Voltage Stability Enhancement of Primary Distribution System by Optimal DG Placement -- Chapter 9: Demand Forecasting Using Artificial Neural Networks- A case study of American Retail Corporation.
Keywords: Computational intelligence; Artificial intelligence; Electric power production; Computational Intelligence; Artificial Intelligence; Electrical Power Engineering